2019
DOI: 10.3889/oamjms.2019.529
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Antibacterial Activity of Plectranthus amboinicus (Lour.) Spreng Leaves Ethanolic Extract as Herbal Mouthwash Against Halitosis Caused Bacteria

Abstract: BACKGROUND: Halitosis is one of the unpleasant conditions which could alter the self-confidence and cause serious illness. One of the treatments to overcome halitosis is by using mouthwash. Plectranthus amboinicus (Lour.) Spreng is one of the plants that is known to have antibacterial activity which can be used to overcome halitosis caused bacteria. AIM: To formulate the Plectranthus amboinicus (Lour.) Spreng leaves ethanolic extract as herbal mouthwash and to evaluate the antibacterial activity against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…In an interesting study, the crude P. amboinicus was used to prepare a mouthwash and the formulation coating only 3% of crude extract was able to inhibit the S. aureus and S. mutans growth, but similar to others studies with extracts the authors can't identify the/or compound(s) responsible by results. In general, the antimicrobial activity is linked, but not conclusively, to presence of phenolic compounds [31] and flavonoids [33], showed to us that further studies about chemical composition and antimicrobial activities for extract are necessary.…”
Section: Carvacrolmentioning
confidence: 99%
See 2 more Smart Citations
“…In an interesting study, the crude P. amboinicus was used to prepare a mouthwash and the formulation coating only 3% of crude extract was able to inhibit the S. aureus and S. mutans growth, but similar to others studies with extracts the authors can't identify the/or compound(s) responsible by results. In general, the antimicrobial activity is linked, but not conclusively, to presence of phenolic compounds [31] and flavonoids [33], showed to us that further studies about chemical composition and antimicrobial activities for extract are necessary.…”
Section: Carvacrolmentioning
confidence: 99%
“…Extracts from different parts from P. amboinicus have been also evaluated, using agar diffusion methods, against several bacteria and the fungus C. albicans. As observed to essential oils S. aureus was the most susceptible strain, but in general, the extracts efficiency is lower than the observed to essential oils because even using higher concentrations the growth inhibition halo are lower diameter when compared to essential oils [22,[29][30][31][32][33][34]. This nature can be linked to the complexity of extracts where even having compounds with proved activity, its concentrations become too low to reach their potential effectiveness.…”
Section: Carvacrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Plectranthus amboinicus species contain antibacterial essential oils such as βcaryophyllene, p-cymene, and γ-terpinenecan. Antibacterial action was shown for P. amboinicus mouthwash by Nazliniwaty and Laila (2019) against Staphylococcus aureus, a bacterium that causes bacterial-induced halitosis, in a study. A salivary sediment model indicated that Punica granatum extract inhibited the production of VSCs by Parvimonas micra, Porphyromonas gingivalis, and Fusobacterium nucleatum bacteria (Veloso et al, 2020).…”
Section: Bad Breath Eliminationmentioning
confidence: 99%
“…Ethanolic extract of Plectranthus amboinicus (Lour.) Spreng leaves can be formulated and used as mouthwash which has antibacterial activity against Staphylococcus aureus and Streptococcus mutans bacteria 17 . Similarly essential oil of Plectranthus amboinicus Lour (malvariço), has been used by the people for the treatment of diseases of the oral cavity, alone or as a mouthwash against a strain of Streptococcus mutans 18 .…”
Section: Quantitative Analysis Of Essential Oil By Gcmentioning
confidence: 99%